PERANG SALIB: PEMICU, PERISTIWA DAN IMPLIKASI - Nawalul Mutawakkil; Yusuf Hanafi (Adisam Publisher, 2025)
This research discusses the Crusades that occurred in the Middle Ages as a series of conflicts between the Christian world of Europe and the Islamic world. The main focus of the research is to analyze the causes, stages, and impacts of the Crusades on both civilizations. The causes of the Crusades involve a combination of religious, political, and economic factors, with the main impetus being the desire to seize Jerusalem from Muslim control. The stages of the Crusades consist of several waves of battles that lasted for more than two centuries, each with different dynamics and outcomes. The impact of the Crusades on the Islamic world includes territorial losses, the resurgence of jihadist spirit, and advancements in military science and technology. Meanwhile, the Western world experienced significant changes in political, trade, and scientific thought aspects, which also contributed to the emergence of the Renaissance. This research provides a comprehensive understanding of the interaction between Islamic and Western civilizations, as well as the impact of the Crusades on the development of world history.